Entecavir and Peginterferon Alfa‐2a in Adults With Hepatitis B e Antigen–Positive Immune‐Tolerant Chronic Hepatitis B Virus Infection. Issue 6 (14th March 2019) - Feld, Jordan J.; Terrault, Norah A.; Lin, Hsing‐Hua S.; Belle, Steven H.; Chung, Raymond T.; Tsai, Naoky; Khalili, Mandana; Perrillo, Robert; Cooper, Stewart L.; Ghany, Marc G.; Janssen, Harry L.A.; Lok, Anna S.; et al.
Abstract : Monotherapy with interferon or nucleoside analog is generally not recommended during the immune‐tolerant (IT) phase of chronic hepatitis B virus (HBV) infection. Recognition that high HBV DNA levels are associated with hepatocellular carcinoma has increased interest in treating HBV in the IT phase. Small pediatric studies reported efficacy with combination nucleoside analog and interferon therapy. The aim of this study was to evaluate the safety and efficacy of the combination of entecavir and peginterferon in adults in the IT phase of chronic HBV infection. Hepatitis B e antigen (HBeAg)–positive adults with HBV DNA > 10 7 IU/mL and alanine aminotransferase (ALT) ≤ 1.5 times the upper limit of normal (ULN) (male: ≤ 45, female: ≤ 30 U/L) received entecavir 0.5 mg daily for 8 weeks followed by the addition of peginterferon alfa‐2a 180 µg/week to entecavir for an additional 40 weeks. The primary endpoint was HBeAg loss and HBV DNA ≤ 1, 000 IU/mL 48 weeks after end of treatment (EOT). Among 28 participants from 11 sites, the median age was 37.2 (range: 22‐61) years, 54% were male, and 96% were Asian. Nearly all were infected with genotype C (64%) or B (32%). Median baseline HBV DNA was 8.2 log10 IU/mL, and ALT was 0.9 times the ULN. Although one (4%) participant cleared HBeAg, none met the primary endpoint of both HBeAg loss AND HBV DNA ≤ 1, 000 IU/mL 48 weeks post‐EOT. ALT elevations > 5 times the ULN occurred in eight (29%) participants, and none were associated with icterus. Forty‐eight weeks posttreatment, HBV DNA rebounded to baseline levels in all participants, including the participant who lost HBeAg, and ALT values returned to near baseline levels in all but four participants. Conclusion : A lead‐in strategy of 8 weeks of entecavir followed by combination peginterferon and entecavir therapy for 40 weeks had limited efficacy in adults in the IT phase of chronic HBV infection and cannot be recommended.